Is cerebral glucose metabolism related to blood–brain barrier dysfunction and intrathecal IgG synthesis in Alzheimer disease?: A 18F-FDG PET/CT study. Issue 37 (September 2016) - Chiaravalloti, Agostino; Fiorentini, Alessandro; Francesco, Ursini; Martorana, Alessandro; Koch, Giacomo; Belli, Lorena; Torniolo, Sofia; Di Pietro, Barbara; Motta, Caterina; Schillaci, Orazio
Abstract : Abstract: The aim of this study was to investigate the relationships between blood–brain barrier (BBB) dysfunction, intrathecal IgG synthesis, and brain glucose consumption as detectable by means of serum/cerebrospinal fluid (CSF) albumin index (Qalb ) and IgG index [(CSF IgG/serum IgG) × Serum albumin/CSF albumin)] and 2-deoxy-2-( 18 F) fluoro-d -glucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) in a selected population affected by Alzheimer disease (AD). The study included 134 newly diagnosed AD patients according to the NINCDS-ADRDA criteria. The mean (±SD) age of the patients was 70 (±6) years; 60 were male and 64 were female. Mini mental State Examination was equal to 18.9 (±7.2). All patients underwent a CSF assay and magnetic resonance before 18 F-FDG PET scanning. The relationships were evaluated by means of statistical parametric mapping (SPM8). We found a significant negative correlation between the increase of Qalb and 18 F-FDG uptake in the Brodmann Area 42 and 22 that corresponds to the left superior temporal gyrus, with higher Qalb values being related to a reduced glucose consumption in these areas. No significant relationships have been found between brain glucose consumption and IgG index. The results of our study suggest that BBB dysfunction is related to reduction of cortical activity in the left temporal cortex in AD subjects.